2022
DOI: 10.1038/s41387-022-00218-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of inflammation in relation to dietary sodium and β-carotene with non-alcoholic fatty liver disease: a mediation analysis

Abstract: Background High sodium intake has been linked to the prevalence of non-alcoholic fatty liver disease (NAFLD), but underlying mechanism remains unclear. This study aims to explore the role of chronic inflammation in the association between sodium and NAFLD. We also observed whether β-carotene, which had a strong anti-inflammatory effect, lowers the odds of NAFLD. Methods We performed mediation analyses to assess the mediating effects of C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Furthermore, dietary fiber also enhances satiety, thus promoting calorie restriction (36). Additionally, fruits and vegetables are rich in antioxidants, including vitamin C, vitamin E, beta-carotene, polyphenols, which neutralize free radicals and mitigate the detrimental effects of oxidative stress on the liver (37)(38)(39)(40)(41). It should also be noted that NAFLD is frequently accompanied by an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dietary fiber also enhances satiety, thus promoting calorie restriction (36). Additionally, fruits and vegetables are rich in antioxidants, including vitamin C, vitamin E, beta-carotene, polyphenols, which neutralize free radicals and mitigate the detrimental effects of oxidative stress on the liver (37)(38)(39)(40)(41). It should also be noted that NAFLD is frequently accompanied by an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] A mediation analysis study using data from the NHANES 2007 to 2010 revealed that dietary β-carotene may decrease the likelihood of NAFLD by suppressing inflammation. [ 34 ] Another case-control study, which recruited 24 control participants and 62 biopsy-proven NAFLD patients, revealed a notable decrease in serum β-carotene levels among NAFLD patients compared to the control group. [ 35 ] Furthermore, serum β-carotene levels gradually decreased with increasing histological severity of NAFLD, implying a potential protective effect of β-carotene on liver pathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, an extreme level of BC intake can cause changes in skin tone along with itching, abdominal cramps, exhaustion, and weight loss. Indeed, the higher dose of β-carotene supplementation also enhances hepatic damage in alcoholic patients [30][31][32]. The pathological mechanism of BC is converting it to vitamin A, which leads to abundant accumulation of vitamin A stored in hepatic stellate cells, causing cellular hypertrophy, excessive biosynthesis of collagen, fibrosis, and hepatic damage [33].…”
Section: Discussionmentioning
confidence: 99%